2021
DOI: 10.2174/1389200222666210223112826
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Metabolism, Distribution, and Excretion of Letermovir

Abstract: Background: Letermovir is approved for prophylaxis of cytomegalovirus infection and disease in cytomegalovirus-seropositive hematopoietic stem-cell transplant (HSCT) recipients. Objective: HSCT recipients are required to take many drugs concomitantly. The pharmacokinetics, absorption, distribution, metabolism, and excretion of letermovir and its potential to inhibit metabolizing enzymes and transporters In vitro were investigated to inform on the potential for drug‒drug interactions (DDIs). Methods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
61
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 15 publications
(61 citation statements)
references
References 0 publications
0
61
0
Order By: Relevance
“…25 The small amount of metabolites together with negligible amounts of drug-related material recovered in urine in a human absorption, distribution, metabolism, and excretion study supported that metabolism and renal excretion play a minor role in the elimination of letermovir. 25 In vitro studies have shown that letermovir is an inhibitor of cytochrome P450 (CYP) 3A4, CYP2C8, and uridine 5 -diphosphoglucuronosyltransferase 1A1/3 and of the efflux transporters P-glycoprotein (P-gp) and breast cancer resistance protein, as well as the hepatic uptake transporters OATP1B1/OATP1B3. 25 In particular, letermovir inactivated CYP3A4/5 (as measured by midazolam 1 -hydroxylation) with a K i value of 35 μM, a K inact value of 0.0473 min -1 and an efficiency (K inact /K i ) of 1.3 min -1 mM -1 .…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…25 The small amount of metabolites together with negligible amounts of drug-related material recovered in urine in a human absorption, distribution, metabolism, and excretion study supported that metabolism and renal excretion play a minor role in the elimination of letermovir. 25 In vitro studies have shown that letermovir is an inhibitor of cytochrome P450 (CYP) 3A4, CYP2C8, and uridine 5 -diphosphoglucuronosyltransferase 1A1/3 and of the efflux transporters P-glycoprotein (P-gp) and breast cancer resistance protein, as well as the hepatic uptake transporters OATP1B1/OATP1B3. 25 In particular, letermovir inactivated CYP3A4/5 (as measured by midazolam 1 -hydroxylation) with a K i value of 35 μM, a K inact value of 0.0473 min -1 and an efficiency (K inact /K i ) of 1.3 min -1 mM -1 .…”
mentioning
confidence: 81%
“…25 In particular, letermovir inactivated CYP3A4/5 (as measured by midazolam 1 -hydroxylation) with a K i value of 35 μM, a K inact value of 0.0473 min -1 and an efficiency (K inact /K i ) of 1.3 min -1 mM -1 . 25 As letermovir is a dual inhibitor and inducer of CYP3A4 in vitro, the net effect of letermovir on CYP3A needed to be studied in a clinical DDI study with a CYP3A probe substrate such as midazolam. Clinical DDI studies with other CYP3A substrates, including cyclosporine A, tacrolimus, and sirolimus, have also been conducted, and these are addressed further in the Discussion section.…”
mentioning
confidence: 99%
See 3 more Smart Citations